First records of the genus Pyrolirion Herb. (Liliopsida, Asparagales, Amaryllidaceae) in Ecuador - Nora H. Oleas; Lou Jost; Ricardo Zambrano C.; Cristian Guzmán Torres; Jorge Heredia; Martin Bustamante; Hugo Romero-Saltos; María Paulina Moreno-Armijos; Alan W. Meerow; Catalina Quintana (Check List)
We report for the first time in Ecuador the small plant genus Pyrolirion Herb. (Amaryllidaceae). We identify several Ecuadorian populations of Pyrolirion tubiflorum (L’Hér.) M. Roem. located in four provinces along the Ecuadorian Andes. This species has been previously recorded in Peru, Bolivia, and Chile. An updated description of P. tubiflorum is provided, along with detailed photographs of some of the Ecuadorian examples of the species.